Nurses' recommendations to the psychoaffective dimensions of patients hospitalized in nephrology - Albert Lengruber de Azevedo; Sílvia Teresa Carvalho de Araújo; João Mário Pessoa Júnior; Lidiane Passos Cunha; Keila do Carmo Neves; Soraia do Socorro Furtado Bastos; Alessandra Guimarães Monteiro Moreira
ABSTRACT Objectives: to analyze nurses' recommendations on the psycho-affective dimensions of patients hospitalized in nephrology. Methods: a qualitative, exploratory and descriptive study, carried out by applying a sociodemographic and training questionnaire, reading a clinical case and conducting a semi-structured interview. Fourteen nurses from a reference hospital in nephrology in the Southeast participated. In the technical input of data treatment, thematic content analysis was used. Results: the recommendations included the exercise of empathy; monitoring of emotions from the implementation of the nursing consultation; continuous sharing of tensions, anxieties and desires; knowledge of one's emotion; increased availability to listen; effectiveness of the approach in teams and social groups. Conclusions: recognizing patients' psycho-affective dimensions, in the context of nurses' performance, favors the expansion of therapeutic listening spaces, welcoming and interpersonal coexistence in nephrology, essential in the production of comprehensive health care.